ASHRAE design guide for tall, supertall, and megatall building systems - Simmonds, Peter, 1954- (ASHRAE, 2015)
"The ASHRAE Design Guide for Tall, Supertall, and Megatall Building Systems is concerned with HVAC, design, maintenance, and other factors for buildings 300 feet (91 m) or higher. The guide details the problems and possible solutions for tall, supertall, and megatall buildings"--